PENTINGNYA ETIKA ISLAM DALAM AKUNTANSI - iswanaji, chaidir (Al Mashalih - Journal of Islamic Law, 2021)
Accounting must refer to the value of justice, truth, and accountability, this is because accounting information has the power to influence thoughts, decision making and actions taken by someone. The accounting profession is a profession that requires the trust of the community. Therefore ethics is very necessary in accounting, so that public trust can be maintained and maintained. This paper tries to explain the importance of ethics in accounting, which is described based on the Islamic perspective. Because Islam is a universal religion, which governs all life including accounting problems. In this paper, it is explained how Islam emphasizes the importance of ethics in accounting.